URBAN LAND REGULARIZATION IN GOIÂNIA: LEGAL HISTORICAL TRAJECTORIES, POLICY MAPPING AND SOCIO SPATIAL TENSIONS - Pereira, Linda Valéria Ribeiro; do Amaral, Gustavo Garcia (Editora Impacto Científico, 2025)
Considering the persistent asymmetries between Brazil’s legal framework and municipal practices of urban land regularization in Goiânia, this paper addresses the gap between the “law” and the “lived city” and its impacts on the right to housing and the social function of property. It aims to analyze the legal-historical trajectory of regularization in the city, identify institutional turning points, and assess the recent effectiveness of instruments (with emphasis on REURB). To this end, we adopt a qualitative design combining: (i) legal mapping of statutes, decrees, plans, and programs; (ii) a hermeneutic reading of constitutional and urban principles; and (iii) a socio-spatial reading of two case studies—Setor Leste Universitário (consolidated central area) and Jardim Nova Esperança (expanding periphery). The results show institutional advances (greater intersectoral coordination and targeting of social-interest areas) coexisting with territorial selectivity and administrative bottlenecks (cadastre, titling, data integration). Findings indicate that effectiveness hinges on aligning inclusion-oriented guidelines (right to the city, social function, adequate housing) with sustained implementation capacity, monitoring, and social participation, which allows us to conclude that long-term policies aligned with urban planning and spatial justice are required.DOI: https://doi.org/10.56238/edimpacto2025.068-006